Current Advances in Meerwein-type Radical Alkene Functionalizations - Diesendorf, Nina; Heinrich, Markus R. (Synthesis, 2022)
Alkene functionalizations via Meerwein arylations are becoming increasingly attractive, especially since a variety of mild and sustainable methods for aryl radical generation are available today. This entails a broad spectrum of substrates and radical scavengers, as well as convenient synthetic routes to relevant precursors for further transformations. The present review focuses on recent advances in Meerwein-type alkene functionalizations and gives insights into the key mechanistic details of the respective reactions.1 Introduction2 Hydroarylation and Carboarylation3 Carboamination, Carbooxygenation, and Carbothiolation4 Carbohalogenation5 Conclusion and Outlook
Keywords: Meerwein arylation; radical chemistry; photocatalysis; olefins; radical-polar crossover